Six-address scheme for multiple hop forwarding in wireless mesh networks - Joseph Kim (2013)
A six field address scheme identifies both the originating point and the endpoint of a data frame enabling multiple hop forwarding through a plurality of intermediate mesh points in a wireless mesh network. Data frames originating or ending at a point outside of the wireless mesh network access the wireless network at a mesh access point using a legacy address scheme. The legacy address schemes are converted to a six address scheme using a proxy address table at the access point. Each mesh access point includes not only a routing table but a proxy address table as well as enabling the mesh access point, and/or mesh portal points, to convert address schemes having less than six address fields to the six field format. Subsequent to the conversion, mesh points within the wireless mesh network need only the routing table to facilitate the forwarding of the data frame.